Prevention of Radial Artery Occlusions Following Coronary Procedures: Forward and Backward Steps in Improving Radial Artery Patency Rates. (October 2018) - Hahalis, George; Tsigkas, Grigorios; Kounis, Nikos; Patsilinakos, Sotirios; Kafkas, Nikolaos; Ziakas, Antonios; Patsourakos, Nikolaos; Almpanis, George; Koniari, Ioanna; Xanthopoulou, Ioanna; Koutsogiannis, Nikolaos; Despotopoulos, Stefanos; et al.
Radial artery (RA) occlusion (RAO) remains the Achilles heel of transradial coronary procedures. Although of silent nature, RAO is relatively frequent, results in graft shortage for future coronary artery bypass surgery, and may occur even after short-lasting, 5F coronary angiography (CAG). The most frequent predictors of RAO are RA size, body size, female gender, and periprocedural anticoagulation intensity. Methods to detect RAO are variable, of which the Barbeau test and ultrasonography have similar diagnostic accuracy. Data indicate that late RAO recanalization may occur. Meticulous handling of RA and the use of appropriate hemostatic devices and techniques along with sufficient heparin dose appear important measures to reduce RAO rates. Recent contradictory studies indicate that the decreasing incidence of RAO overtime is not as uniform as previously thought. In 2 meta-analyses, the benefit of higher over lower anticoagulation intensity became evident. As "it may all be appropriate anticoagulation" for a simplified approach against RAO, the results of an ongoing trial comparing 100 with 50 IU/kg body weight in transradial CAG are eagerly awaited.